Porous membranes designed from bi-phasic polymeric blends containing silver decorated reduced graphene oxide synthesized via a facile one-pot approach. Issue 41 (7th May 2015) - Kumar S Mural, Prasanna; Sharma, Maya; Shukla, Abhinaya; Bhadra, Sambhu; Padmanabhan, Babu; Madras, Giridhar; Bose, Suryasarathi
<x xml:space="preserve">Abstract</x> In this work, porous membranes were designed by selectively etching the PEO phase, by water, from a melt-mixed PE/PEO blend.